1995
DOI: 10.1259/0007-1285-68-812-841
|View full text |Cite
|
Sign up to set email alerts
|

Does peppermint oil relieve spasm during barium enema?

Abstract: The effectiveness of topical peppermint oil added to barium sulphate suspension in relieving colonic muscle spasm during double contrast barium enema examination was assessed in a double blind study. 141 patients were randomized either to a control group (71 patients) examined with standard barium suspension or to the treatment group which received peppermint oil mixed with the barium preparation. No residual spasm was evident in a significant proportion of patients in the treated group (60%) compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Peppermint oil has been demonstrated to be a useful antispasmodic agent for upper GI endoscopy [9], colonoscopy [10,11], and barium enema examination [12,13]. Recently, we reported that topical treatment with L-menthol, the major constituent of peppermint oil, effectively suppressed gastric peristalsis in a multicenter, randomized, double-blind, placebo-controlled trial [14].…”
Section: Introductionmentioning
confidence: 99%
“…Peppermint oil has been demonstrated to be a useful antispasmodic agent for upper GI endoscopy [9], colonoscopy [10,11], and barium enema examination [12,13]. Recently, we reported that topical treatment with L-menthol, the major constituent of peppermint oil, effectively suppressed gastric peristalsis in a multicenter, randomized, double-blind, placebo-controlled trial [14].…”
Section: Introductionmentioning
confidence: 99%
“…Its extract, peppermint oil, has been shown to have various therapeutic effects such as alleviating tension-type headaches [9], relieving non-ulcer dyspepsia, [10] reducing colonic spasm during barium examination, [11,12] and antiviral activity against HSV-1 and HSV-2 [13] either alone or in combination. Peppermint oil, and its major constituent, menthol, also has relaxing effects on gastrointestinal smooth muscle by blocking Ca 2?…”
Section: Introductionmentioning
confidence: 99%
“…The use of pharmacological agents to bring about smooth muscle relaxation. This includes the use of glucagon intravenously [17], and peppermint oil, added to the barium sulphate suspension [18]. The short-acting anti-muscarinic hyoscine-N-butyl bromide (Buscopan) has now overtaken glucagon as the most commonly used anti-spasmodic agent outside the United States [19,20].…”
Section: Discussionmentioning
confidence: 99%